PERSEPSI GURU PAMONG TERHADAP KOMPETENSI PEDAGOGIK MAHASISWA JURUSAN PIIS YANG MELAKUKAN PPL-2 DI SMA - Desi Ruspayanti; Endang Purwaningsih; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the perception of civil servant teachers on thepedagogic competence of students majoring in Social Sciences Education whocarried out PPL-2 in 2017 at SMA Santun Untan Pontianak. The researchmethod used is qualitative in the form of descriptive research. The source of thisresearch data is PPL student tutors who teach Economics, Sociology, History,PKN, Geography subjects. The data collection tools used are interviewguidelines and literature/documents. Data collection techniques usinginterviews and documentation. The results of this study indicate that, based onthe perceptions of the civil servant teachers, students are able to understandlearning theories and educational learning principles such as being able toexplain learning activities/activities, curriculum development such as makinglesson plans are in accordance with the school curriculum and able to conveymaterial well, the potential development of students has also been able to carryout, communication with students such as asking questions and answeringquestions, assessment and evaluation. While the competencies that have notbeen mastered by PPL students are understanding the character of students,which is caused by a lack of approach to students, and in educational learningactivities students also have not mastered as in managing classes, students arestill unable to create and have not been able to adjust the time in the learningprocess. teaching takes place.Keywords: Perception, Pedagogy, PPL Students